2015
DOI: 10.1016/j.ijgo.2015.07.022
|View full text |Cite
|
Sign up to set email alerts
|

A clinical evaluation of bleeding patterns, adverse effects, and satisfaction with the subdermal etonogestrel implant among postpartum and non‐postpartum users

Abstract: The etonogestrel implant (Implanon; Merck Sharp and Dohme, Kenilworth, NJ, USA) is an effective contraceptive with a good safety profile for up to 3 years [1]. However, its adverse effects include irregular vaginal bleeding (affecting 68.0% of users), weight gain (20.7%), acne (15.3%), breast pain (9.1%), and headache (8.5%) [2]. To provide further information about contraception options for women in the postpartum period, the aim of the present study was to investigate the bleeding patterns and adverse effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Seven studies looked at post‐partum insertion as a predictor, either as a primary or secondary variable 9–11,13,15,17 , 19 . None found statistically significant differences in unfavourable bleeding patterns between post‐partum and non‐post‐partum insertion.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Seven studies looked at post‐partum insertion as a predictor, either as a primary or secondary variable 9–11,13,15,17 , 19 . None found statistically significant differences in unfavourable bleeding patterns between post‐partum and non‐post‐partum insertion.…”
Section: Resultsmentioning
confidence: 99%
“…None of the seven studies which assessed or reported the effect of post-partum status showed an effect on bleeding pattern. [9][10][11]13,15,17,19 Breastfeeding is likely to influence bleeding patterns since exclusive breastfeeding can inhibit ovulation, but it was reported in only two of the seven papers which included post-partum women. 11,17 In one of these, 11 a retrospective study, breastfeeding at the time of insertion is recorded but not at the time of reported bleeding complaints.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations